Parents’ Education Anxiety and Children’s Academic Burnout: The Role of Parental Burnout and Family Function - Wu, Kai; Wang, Feng; Wang, Wei; Li, Yongxin (Frontiers in Psychology, 2022)
This study aimed to explore the effect of parents’ education anxiety on children’s academic burnout, and the mediation effect of parental burnout and the moderating effect of family function. A total of 259 paired parents and children from two middle schools in central China participated in the survey. The questionnaire was conducted using the Educational Anxiety Scale, Parental Burnout Scale, Adolescent Student Burnout Inventory, and Family APGAR Index. Our results indicated that parental education anxiety had a positive predictive effect on children’s academic burnout. Moreover, parental burnout played a complete mediating role between parents’ education anxiety and children’s academic burnout. Finally, the relationship between education anxiety and parental burnout was moderated by family function, and higher family function buffered the effect of education anxiety on parental burnout. The results suggest the mechanism of parental education anxiety on children’s academic burnout, and the role of family function in alleviating parental burnout.